THE ROLE OF THE LEADER IN THE SYSTEMATIC ORGANIZATION OF MANAGEMENT RELATIONS - Bobirmirzo Arzimatov (American Journals, 2023)
The article mainly contains opinions on leadership qualities and how a leader should work with employees, as well as what kind of image a leader should have.
Keywords: Leader, employee, virtue, speech, public speaking, sincere look, team, individual group.